Gender Pay Gap in the Construction Industry: Evidence from Morang District, Nepal - Thapa, Hom Bahadur; Acharya, Krishna Prasad; Khatiwada, Sita Ram (Academic Journal of Sukuna, 2025)
The issue of gender-based wage differentials in the construction industry has profound historical roots tracing back to early human societies where labor was divided by gender. This long-standing division has evolved but persisted, evident in today’s global workforce, including in sectors like construction, where such disparities are noticeable. The study focuses on measuring and analyzing these gender-based wage differentials within Sundarharaincha-12, Morang in Nepal, employing a quantitative research design. The methodology involves structured questionnaires aimed at capturing data from 50 sample sizes of construction workers on wages, job roles, educational background, and personal demographics to provide a comprehensive analysis of the factors contributing to wage disparities. Despite legal mandates for equal pay, significant disparities persist, with women earning approximately 16% less than their male counterparts for similar work. The findings underscore a significant gender-based wage gap, with women predominantly in lower-wage roles and virtually absent from higher-paying positions like masonry or contracting. The study recommends that Enforce policies that guarantee equal pay for equal work, irrespective of gender, particularly in labor-intensive roles and offer training and education, especially for women, to help them qualify for higher-paying roles such as masons or contractors. By addressing these issues, there is potential not only to enhance gender equality but also to improve the overall productivity and efficiency of the construction sector in developing regions like Nepal.